The Supernatural Media Virus Virus Anxiety in Gothic Fiction Since 1990 - Schmitz, Rahel Sixta (Gegenwartsliteratur, 2021)
Since the 1990s, the virus and the network metaphors have become increasingly popular, finding application in a broad range of everyday discourses, academic disciplines, and fiction genres. In this book, Rahel Sixta Schmitz defines and discusses a trope recurring in Gothic fiction: the supernatural media virus. This trope comprises the confluence of the virus, the network, and a deep, underlying media anxiety. This study shows how Gothic narratives such as House of Leaves or The Ring feature the supernatural media virus to negotiate as well as actively shape imaginations of the network society and the dangers of a globalized, technologized world.